6x+27+90=7x-9

Simple and best practice solution for 6x+27+90=7x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+27+90=7x-9 equation:



6x+27+90=7x-9
We move all terms to the left:
6x+27+90-(7x-9)=0
We add all the numbers together, and all the variables
6x-(7x-9)+117=0
We get rid of parentheses
6x-7x+9+117=0
We add all the numbers together, and all the variables
-1x+126=0
We move all terms containing x to the left, all other terms to the right
-x=-126
x=-126/-1
x=+126

See similar equations:

| 5a+4a+5a-8a=18 | | 5z-z-3z=14 | | 36-3(2x-6)=30(x-x) | | 141+127+8y=180 | | 7x+6-3x2=0 | | (y+8)^2=-21 | | 19x-28=2(x+7) | | -35=x=28 | | 180=c+17+107 | | n/4+9=6 | | 13g-8g=20 | | 10r-11r+15r-r=14 | | 1/2x-8=-5.5 | | -68-8x=-x+72 | | 16-4x=180 | | 4x+3-1=2(2x=2)-2x | | -3(5+15z)=5(-9z-3) | | 3d+6d-7d=10 | | 10x-16=4x+34 | | 3.9=1.5(2.2–1.2x) | | 1/2x-8=5.5 | | 10^x=2^x-22 | | -7x+5(1-8x)=0 | | 9s-9s+4s-2s+s=15 | | 14k-8k=12 | | z+1.8=12.1 | | 5x/4-x=x12-4/3 | | 36.7h=23.50h+53 | | 14=3-2x | | 5(n+1)-2n=14 | | 3m+4m+6=50 | | z+8=221 |

Equations solver categories